PRELIMINERY STUDY NICKEL RECYCLING FROM WASTE MATERIAL BY HYDROMETALLURGYCAL PROCESS - RIFKI S. AL. Y., MOH.
This research has studied the possibility to extract nickel from waste materials containing nickel as well as copper, zinc, iron, aluminum and phosphor. The waste material is supplied by Malaysia Lab Zinc Company. The leaching experiment was done using waste material after being roasted at 400oC for two hours to reduce water content and volatile matter. A series of leaching test has been conducted in 200 ml sulfuric acid solutions containing 51.65 gpl (10.33 gr), 62 gpl (12.4 gr) and 77.5 gpl (15.5 gr) for 2, 4, 6, 8, 12 and 24 hours. Effect of temperature in the leaching process are assessed by conducting leaching tests at temperature 50, 65, 80 degrees C in 62 gpl sulfuric acid solutions for 30 minute, 1, 2, 4, 6, 8 and 12 hours. Dissolved copper is then removed from the solution by cementation process using iron powder at room temperature. Iron precipitation is done after Cu cementation and this is carried out by adding one gram KMnO4 to oxidize Fe2+ into Fe3+ which is followed by pH adjustment. The remaining copper and iron are then removed from solution by ion exchange using resin Lewatit Monoplus TP 207 XL.In this research, kinetics behavior of nickel oxide dissolution from waste material is also studied. Kinetic model referred in this research is shrinking core. Rate controlling step is then determined based in the most suitable kinetic model and the value of its activation energy. The highest percent extraction of Ni, Cu and Zn in these leaching test is achieved in 77.5 gpl of sulfuric acid at 80oC for 24 hours. Percent extraction of Ni, Cu and Zn are 64.838%, 94.34% and 98.82%. Copper removal by cementation process at room temperature for two hours has reduced copper ion up to 81.67% (from 506.24 mg down 92.77 mg). The decrease of the amount of ferrous ion during iron precipitation in the solutions by pH adjustment is 92.415% (decrease from 853.977 mg to 64.773 mg). Ion exchange experiment has reduced iron and copper ion up to 68.25% and 26.5% respectively.